Ocular Findings in Infants with Microcephaly Caused by Presumed Congenital Infection by Zika Virus in Sergipe - Marco Valadares; Anne Carolyne Lelis Oliveira Pedroso; Alessandro Santana; Angela Maria da Silva; Isabela Soares Costa; Maria Luiza Doria Almeida; Roque Pacheco de Almeida (Journal of Ophthalmology)
This study aims at identifying ocular findings in infants with microcephaly associated with presumed intrauterine infection by ZIKV. A cross-sectional study included 62 outpatient infants with congenital microcephaly, presumably secondary to maternal ZIKV infection. The included infants had head circumference below −2 standard deviations, with negative maternal serology for toxoplasmosis, rubella, cytomegalovirus, syphilis, and HIV. Assessment of ocular alterations was performed through review of their medical records. Forty two (67.7%) of the children analyzed presented some degree of ocular alteration. Findings in the posterior segment occurred in 29 (46.8%) patients, including atrophy of the retinal pigmentary epithelium in 15 (24.2%) patients, chorioretinal scars in 14 (22.6%) patients, retinal coloboma in 6 (9.7%) patients, and punctate retinal hemorrhage in 1 (1.6%) patient. Other ocular alterations were seen in 15 (24.2%) patients, including pathological strabismus in 11 (17.7%) patients, congenital cataracts in 2 (3.2%) patients, and nystagmus in 2 (3.2%) patients. Functional alterations were seen in four (6.5%) children. More than one change occurred in 11 (17.7%) children, eight of whom had head circumferences below −3 standard deviations. Changes in both the eyes occurred in 22 (35.5%) children, while 20 (32.3%) children had unilateral involvement. Among the 42 children with any ocular alteration, 27 (64.3%) children presented with severe microcephaly (head circumference with standard deviation lower than −3). The majority of children with microcephaly, presumably secondary to maternal ZIKV infection, present ocular alterations, with a higher frequency of involvement in the fundus. Severe ocular alterations are related to severe microcephaly.